Relative frequency, clinical, neuroimaging, and postsurgical features of pediatric temporal lobe epilepsy - Sales,L.V. (2006)
We describe the relative frequency, clinical features, neuroimaging and pathological results, and outcome after pharmacological or surgical intervention for a series of pediatric patients with temporal lobe epilepsy (TLE) from an epilepsy center in Brazil. The medical records of children younger than 12 years with features strongly suggestive of TLE were reviewed from January 1999 to June 1999. Selected children were evaluated regarding clinical, EEG, and magnetic resonance imaging (MRI) investigation and divided into three groups according to MRI: group 1 (G1, N = 9), patients with hippocampal atrophy; group 2 (G2, N = 10), patients with normal MRI, and group 3 (G3, N = 12), patients with other specific temporal lesions. A review of 1732 records of children with epilepsy revealed 31 cases with TLE (relative frequency of 1.79%). However, when the investigation was narrowed to cases with intractable seizures that needed video-EEG monitoring (N = 68) or epilepsy surgery (N = 32), the relative frequency of TLE increased to 19.11 (13/68) and 31.25% (10/32), respectively. At the beginning of the study, 25 of 31 patients had a high seizure frequency (80.6%), which declined to 11 of 31 (35.5%) at the conclusion of the study, as a consequence of pharmacological and/or surgical therapy. This improvement in seizure control was significant in G1 (P < 0.05) and G3 (P < 0.01) mainly due to good postsurgical outcome, and was not significant in G2 (P > 0.1, McNemar's test). These results indicate that the relative frequency of TLE in children was low, but increased considerably among cases with pharmacoresistant seizures. Patients with specific lesions were likely to undergo surgery, with good postoperative outcomes.